Quality Control Analysis of Sugar Production Process with FTA and FMEA Methods in PT XYZ - Mardila Nur Imamah; Rr. Rochmoeljati (Universitas KH. Abdul Chalim Mojokerto, 2025)
One of the sugar factories built by the Indonesian state as an effort to revitalize the national sugar industry through the use of modern technology is PT XYZ. However, this sugar factory is experiencing problems with the results of testing the production of white crystal sugar which has defects that are not in accordance with the quality requirements of white crystal sugar with SNI number 3140-3: 2020. Defects that occur include defects in sugar moisture content, sugar solution color, grain size, and sugar crystal uniformity. This study was conducted to determine the factors that can affect the occurrence of defects in the white crystal sugar production process at PT XYZ and how the proposed improvements can be implemented to control the quality of white crystal sugar products at PT XYZ. The methods used in this research are the Fault Tree Analysis (FTA) and Failure Mode and Effects Analysis (FMEA) methods. Based on calculations using the Fault Tree Analysis method, the calculated probability results for each type of defect, namely large grain defects, moisture content, color, and sugar crystal uniformity, are 0.000657%, 0.000889%, 0.001597%, and 0.000662%, respectively. The FMEA method obtained a large grain type defect with the highest RPN value of 120 (High). Large grain type defects cause white crystal sugar to not conform to market specifications and dissolve more slowly. In the second rank, there is a defect in water content with an RPN value of 112 (medium). Quality control should be carried out regularly and continuously so that it can be a reference for continuous improvement in the future.